The mail art collection of the XVI São Paulo Biennial: themes, typologies and thechniques - Romano, Camila Bôrtolo (DAT Journal, 2021)
This article is a study of the mail art collection of the XVI Biennial of São Paulo that is part of the City Art Collection (CAC) under guard of the São Paulo Cultural Center (CCSP). It seeks to identify the main themes, typologies and techniques used by the artists who participated in the XVI Biennial of São Paulo that. For this, we will perform a sampling of the works based on the themes defined by Fabiane Pianowski and the analysis of the different typologies and techniques present in the works that make up the collection.